2021
DOI: 10.1093/eurheartj/ehab314
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism in patients with COVID-19: incidence, risk factors, clinical characteristics, and outcome

Abstract: Aims We investigated the incidence, risk factors, clinical characteristics, and outcomes of pulmonary embolism (PE) in patients with COVID-19 attending emergency departments (EDs), before hospitalization. Methods and Results We retrospectively reviewed all COVID-19 patients diagnosed with PE in 62 Spanish EDs (20% of Spanish EDs, case group) during the first COVID-19 outbreak. COVID-19 patients without PE and non-COVID-19 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
73
6
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 14 publications
9
73
6
7
Order By: Relevance
“…Furthermore, our database shows that mortality was significantly greater for COVID-19 patients with PE versus COVID-19 patients without PE. This result contrasts with a previous study [ 24 ] which found no difference . This might be due to the greater power of our national data or to national differences in patient management.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our database shows that mortality was significantly greater for COVID-19 patients with PE versus COVID-19 patients without PE. This result contrasts with a previous study [ 24 ] which found no difference . This might be due to the greater power of our national data or to national differences in patient management.…”
Section: Discussioncontrasting
confidence: 99%
“…Further investigations will be needed to clarify the relationship between deep vein thrombosis (DVT) and PE in COVID-19 and in comparison with other ARDS. As suggested in metanalyses on DVT and PE [ 24 , 31 ], there is a major to identify the proportion of PE resulting from DVT embolism and the proportion resulting from COVID-19 pulmonary vasculopathy. The endothelial effect of ARDS, which is well-known, is more correlated with duration of disease than with a specific cause [ 32 , 33 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike a consistent finding with an apparently high prevalence of thromboembolic events among patients with COVID-19 infection in western countries, the ethnic difference remains an essential issue with regard to the prevalence of thromboembolic events and the need for routine thromboprophylaxis among patients with COVID-19 infection in Asian countries, highlighting the need for real-world data on thromboembolic events in the Asian population [7][8][9][10]. Additionally, recent studies have implicated neutrophilic inflammatory response, particularly neutrophil extracellular traps (NETs), with the pathogenesis of thrombosis formation in COVID-19 infection [11].…”
Section: Introductionmentioning
confidence: 81%
“…Recent evidence has found highly prevalent thromboembolic events, including deep venous thrombosis (DVT), pulmonary embolism (PE) and acute ischemic stroke, in patients with COVID-19 infection, and D-dimer has been attributed as an essential biomarker for thromboembolic events in patients with COVID-19 infection [4][5][6]. Miro et al, investigating 74,814 patients with COVID-19 with 1,388,879 non-COVID-19 controls in Spain, recently reported that the incidence of PE in patients with COVID-19 was approximately nine-fold higher than those in the non-COVID-19 population (310 vs. 35 per 100,000 person-years) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary embolism (PE) can contribute to a sudden deterioration in oxygen exchange. Although unusual in COVID-19 patients (around 0.5%), the incidence is approximately nine times higher than in the general population [78,79]. The upregulation of miR-9 in SARS-CoV-2 infection dysregulates transcription factor EP300, which increases plasminogen activator inhibitor 1 (PAI-1).…”
Section: Coagulopathymentioning
confidence: 99%